2010
DOI: 10.3390/md8030629
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Cyclopeptides as Lead Compounds to Novel Targeted Cancer Drugs

Abstract: Cyanobacterial cyclopeptides, including microcystins and nodularins, are considered a health hazard to humans due to the possible toxic effects of high consumption. From a pharmacological standpoint, microcystins are stable hydrophilic cyclic heptapeptides with a potential to cause cellular damage following uptake via organic anion-transporting polypeptides (OATP). Their intracellular biological effects involve inhibition of catalytic subunits of protein phosphatase 1 (PP1) and PP2, glutathione depletion and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 181 publications
(207 reference statements)
0
52
0
Order By: Relevance
“…Due to the inhibitory effect on PP, the acute toxins, microcystins and nodularins, are also considered to be potential anticancer drug candidates (Monks et al, 2007;Sainis et al, 2010). In mammalian organisms exposed to microcystins, the toxins cross cell membranes of hepatocytes through the organic anion-transporting polypeptides (OATP).…”
Section: Inhibition Of Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the inhibitory effect on PP, the acute toxins, microcystins and nodularins, are also considered to be potential anticancer drug candidates (Monks et al, 2007;Sainis et al, 2010). In mammalian organisms exposed to microcystins, the toxins cross cell membranes of hepatocytes through the organic anion-transporting polypeptides (OATP).…”
Section: Inhibition Of Enzyme Activitymentioning
confidence: 99%
“…As a consequence, the cancer cells are more sensitive to MCs and experience cytotoxic effects at lower concentrations than normal cells. Work on MC variants with high selectivity against cancer-specific OATPs is in progress (Monks et al, 2007;Sainis et al, 2010).…”
Section: Inhibition Of Enzyme Activitymentioning
confidence: 99%
“…The secondary metabolites produced in cyanobacteria play an important role in toxicity as iron chelators, protease inhibitors, growth inhibitors as well as growth promoting properties and have been well documented [Prasanna et al, 2010;Yadav et al, 2011]. Some metabolites such as microcystins, saxitoxins or anatoxins, are of global signifi cance because of their toxicity while other display signifi cant pharmaceutical potential [Sainis et al, 2010]. It has been found that the cyanotoxins, anatoxin-a, microcystins and cylindrospermopsin obtained from Anabaena, Microcystis and Cylindrospermopsis (respectively), show larvicidal activity with >50% mortality.…”
Section: Production Of Secondary Metabolites With Biological Activitymentioning
confidence: 99%
“…Since, there is a commonality of the control of cancer types broadly by the inhibition of a target protein, responsible for the origin of cancer stem cells (Costa et al 2012;Dixit and Suseela 2013), it can be envisaged that the concept of the development of ADCs, in a systematic approach, could be widely adopted with the involvement of a natural compound. The development of emulative and efficacious drugs for the diverse cancer types, individually as well as holistically, is still an elusive goal in pharmaceutics, today; and bioactive compounds of Lyngbya are used to target cancer macromolecules, tubulin or actin filaments, protein kinase, microtubule, calcium influx, serine proteases, caspase, Bcl-2 protein, voltage-gated sodium channel and cancer related secretary pathways inhibition in eukaryotic cells (Márquez et al 1998;Newman and Cragg 2004;Perez et al 2005;Simmons et al 2005;Watanabe et al 2006;Tabuchi et al 2009;Oftedal et al 2010;Sainis et al 2010).…”
Section: Cyanobacterial Bioactive Molecules Under Clinical Trialsmentioning
confidence: 98%